Strategi Pendidikan Karakter Anak Usia Dini Berbasis "PUDAK" sebagai Kearifan Lokal Gresik - Novita Widiyaningrum (Andragogi: Jurnal Pendidikan dan Pembelajaran, 2026)
Character education is a fundamental foundation for shaping children's personalities from an early age and cannot be separated from local culture. This study analyzes the strategies, challenges, and solutions of educational institutions in fostering children's character through PUDAK's local wisdom in Gresik Regency. Using a qualitative case study approach, the research was conducted at Dikara Edu Center (DEC) Miru Kedamean, an informal institution that uses PUDAK, a traditional Gresik food, as a medium for early childhood character education. Data were collected through participatory observation, semi-structured interviews with the founder, teachers, and parents, and documentation, then analyzed using Yin's case study model. Results show that DEC implements a contextual, integrative, sustainable strategy through play, habituation, role modeling, group work, and age-appropriate tasks. Major challenges include limited learning time, differing emotional development, behavioral inconsistency, and weak continuity between school and home; solutions include gradual habituation, flexible activities, consistent routines, and active parental collaboration. Theoretically, these findings extend Stuart Hall's identity theory by showing that subject formation also occurs through sensory habituation and institution-family synergy rooted in local wisdom. The study confirms that PUDAK-based education effectively and sustainably builds children's character.